2022
DOI: 10.3389/fgene.2022.968711
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture treatment on microRNAs expression in ovarian tissues from Tripterygium glycoside-induced diminished ovarian reserve rats

Abstract: Acupuncture is widely used to improve ovarian function. Previously, we demonstrated that acupuncture can improve oxidative stress in rats with tripterygium glycoside tablet suspension (TG)-induced diminished ovarian reserve (DOR). Herein, we aimed to explore the antioxidation mechanism of acupuncture for ameliorating the ovarian reserve in DOR rats. We performed microRNA sequencing and bioinformatics analysis to screen differentially expressed miRNAs (DE miRNAs) in ovarian tissues. In total, 1,172 miRNAs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…( 39 ) found that electro-acupuncture could increase primordial follicle counts, E 2 and AMH levels, while decreasing FSH and LH levels by targeting the PI3K/AKT/mTOR signaling pathway. Another study indicated that acupuncture could inhibit bta-miR-7857-3p_R-1, mdo-miR-26b-5p_R+1_1ss10TC, and rno-miR-92b-3p expression in ovarian tissues and improve ovarian function via relieving DOR-mediated oxidative stress ( 18 ). Besides, some investigations also found acupuncture could reduce granulosa cell autophagy by weakening the expression of LncMEG3 and regulating the PI3K/AKT/mTOR pathway ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 39 ) found that electro-acupuncture could increase primordial follicle counts, E 2 and AMH levels, while decreasing FSH and LH levels by targeting the PI3K/AKT/mTOR signaling pathway. Another study indicated that acupuncture could inhibit bta-miR-7857-3p_R-1, mdo-miR-26b-5p_R+1_1ss10TC, and rno-miR-92b-3p expression in ovarian tissues and improve ovarian function via relieving DOR-mediated oxidative stress ( 18 ). Besides, some investigations also found acupuncture could reduce granulosa cell autophagy by weakening the expression of LncMEG3 and regulating the PI3K/AKT/mTOR pathway ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these may account for adverse risks like ovarian hyperstimulation syndrome, venous thromboembolism, stroke, and breast cancer ( 15 , 16 ). Owing to these side effects, an increasing number of patients with DOR have sought complementary and alternative medicine based on growing clinical evidence, such as acupuncture, to improve treatment outcomes ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%